Return to sport after surgical management of posterior shoulder instability: A systematic review and meta-analysis - Gouveia, K.; Kay, J.; Memon, M.; Simunovic, N.; Bedi, A.; Ayeni, O. R. (The American Journal of Sports Medicine, 2022)
Background: Posterior shoulder instability accounts for a small proportion of all shoulder instability, although it can affect athletes of all types, from contact to overhead athletes. Surgical treatment is quite successful in these patients; however, the literature reports a wide range of rates of return to sport.